Association of Systemic Inflammation and Malnutrition With Survival in Nasopharyngeal Carcinoma Undergoing Chemoradiotherapy: Results From a Multicenter Cohort Study - Wang, Xin; Yang, Ming; Ge, Yizhong; Tang, Meng; Rao, Benqiang; Chen, Yongbing; Xu, Hongxia; Cong, Minghua; Guo, Zengqing; Shi, Hanping (Frontiers in Oncology, 2021)
Background Malnutrition and systemic inflammation are common in patients with nasopharyngeal carcinoma (NPC). The Patient-Generated Subjective Global Assessment (PG-SGA) score and neutrophil-to-lymphocyte ratio (NLR) reflect the integrated nutritional status and inflammatory level of patients with NPC, respectively. We performed this study to identify whether NLR and PG-SGA score are associated with outcome and survival time for patients with NPC undergoing chemoradiotherapy. Methods The multicenter cohort study included 1,102 patients with NPC between June 2012 and December 2019. The associations of all-cause mortality with NLR and PG-SGA score were calculated using the Kaplan–Meier method and the log-rank test. We also did a multivariate-adjusted Cox regression analysis to identify the independent significance of different parameters. Restricted cubic spline regression was carried out to evaluate the association between NLR and overall survival (OS). A nomogram was established using the independent prognostic variables. Interaction terms were used to investigate whether there was an interactive association between NLR and PG-SGA. Results A total of 923 patients with NPC undergoing chemoradiotherapy were included in this study: 672 (72.8%) were males and 251 (27.2%) were females, with a mean age of 49.3 ± 11.5 years. The Kaplan–Meier curves revealed that patients with malnutrition (PG-SGA score >3) had worse survival than patients who were in the well-nourished group (PG-SGA score ≤3) (p < 0.0001). In addition, patients in the high NLR group (NLR ≥ 3) had worse survival than those in the low NLR group (NLR < 3) (p < 0.0001). Patients with high PG-SGA and high NLR had the worst survival (p < 0.0001). An increase in NLR had an inverted L-shaped dose–response association with all-cause mortality. A nomogram was developed by incorporating domains of NLR and PG-SGA score to accurately predict OS 12–60 months for patients [the C-index for OS prediction of nomogram was 0.75 (95% CI, 0.70–0.80)]. The interaction of PG-SGA with NLR was significant (p = 0.009). Patients with high PG-SGA and high NLR had a nearly 4.5-fold increased risk of death (HR = 4.43, 95% CI = 2.60–7.56) as compared with patients with low PG-SGA and low NLR. Conclusions Our study provided clear evidence that high PG-SGA score and high NLR adversely and interactively affects the OS of patients with NPC undergoing chemoradiotherapy.